2021
DOI: 10.1093/fampra/cmab023
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic uncertainty in primary care: what is known about its communication, and what are the associated ethical issues?

Abstract: Background Diagnostic uncertainty (DU) in primary care is ubiquitous, yet no review has specifically examined its communication, or the associated ethical issues. Objectives To identify what is known about the communication of DU in primary care and the associated ethical issues. Methods Systematic review, critical interpretive synthesis and ethical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…This implies that sharing uncertainty may be more common than reported, a noteworthy finding especially in this time-pressured acute care setting. In our study uncertainty expressions can be depicted as a communication strategy and a way to explain diagnostic reasoning to patients, something suggested in previous studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 95%
“…This implies that sharing uncertainty may be more common than reported, a noteworthy finding especially in this time-pressured acute care setting. In our study uncertainty expressions can be depicted as a communication strategy and a way to explain diagnostic reasoning to patients, something suggested in previous studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 95%
“…There were limited findings regarding uncertainty, compared with those concerning risk. Uncertainty in medicine is an under-researched area3 54–56 thus eRATs are influencing aspects of the consultation which are already poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, reasoning under uncertainty is a linchpin of human cognition (Lake et al 2017) and has been shown to be a central component of "good" decision-making (Laidlaw and Russell 2021;Bhatt et al 2021). Fields which have traditionally de-emphasized uncertainty, such as in the medical profession, are now encouraging trainees to recognize and thoroughly consider when there is uncertainty in a diagnosis or treatment plan in an effort to improve medical safety (Hall 2002;Platts-Mills, Nagurney, and Melnick 2020;Cox et al 2021). Hence, annotation schemes which enable the expression of probability judgements, particularly in datasets wherein the underlying "ground truth" or the "true" label is unknown, are sensible and desirable for improving ma- chine safety, trustworthiness, and efficacy.…”
Section: Discussionmentioning
confidence: 99%